Traveling in time and space: spiritual and ideological aspects of contacts between Russia and Ethiopia in the late 19th — early 20th century - Alexander Polunov (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2025)
The article is devoted to the spiritual and ideological aspects of interaction between the Russian Empire and Ethiopia (Abyssinia) at the end of the 19th – beginning of the 20th centuries. Relations between the two Christian states can be described as “a journey through time,” since from the point of view of Russian society, Ethiopia not only remained faithful to the original religion and traditional way of life, but was also in many ways similar to pre-Petrine Rus'. Here the role of the clergy was strong; the head of the state was the Negus, endowed with autocratic power. Parallels with Russia were also visible in the social structure of the African country. The spiritual and religious dialogue between Russia and Ethiopia was manifested in a number of symbolic gestures, mutual visits, and other measures of an ideological nature. Despite the fact that for a long time the idea of friendship with the country of “black Christians” captivated the minds of conservative public and church leaders in Russia, due to the political complications of the early 20th century the “empire of kings” gradually lost interest in “time travel” associated with Ethiopia. The very perception of the African country as the embodiment of the historical past lost its basis as its isolation from the outside world collapsed. By the beginning of the twentieth century. Ethiopia became a subject of interest of Western powers, whose attitudes were dictated more by pragmatic rather than spiritual and ideological considerations. The collapse of the Russian monarchy interrupted relations between Russia and Ethiopia for a long time. Nevertheless, these relations represent a remarkable page in the history of Russian public thought.